Negative perceptions of aging and decline in walking speed: A self-fulfilling prophecy - Kenny, Rose; Robertson, Deirdre (My University, 2015)
Introduction Walking speed is a meaningful marker of physical function in the aging population. While it is a primarily physical measure, experimental studies have shown that merely priming older adults with negative stereotypes about aging results in immediate declines in objective walking speed. What is not clear is whether this is a temporary experimental effect or whether negative aging stereotypes have detrimental effects on long term objective health. We sought to explore the association between baseline negative perceptions of aging in the general population and objective walking speed 2 years later. Method 4,803 participations were assessed over 2 waves of The Irish Longitudinal Study on Ageing (TILDA), a prospective, population representative study of adults aged 50+ in the Republic of Ireland. Wave 1 measures – which included the Aging Perceptions Questionnaire, walking speed and all covariates - were taken between 2009 and 2011. Wave 2 measures – which included a second measurement of walking speed and covariates - were collected 2 years later between March and December 2012. Walking speed was measured as the number of seconds to complete the Timed Up-And-Go (TUG) task. Participations with a history of stroke, Parkinson’s disease or an MMSE < 18 were excluded. Results After full adjustment for all covariates (age, gender, level of education, disability, chronic conditions, medications, global cognition and baseline TUG) negative perceptions of aging at baseline were associated with slower TUG speed 2 years later (B=.03, 95% CI = .01 to 05, p< .05). Conclusions Walking speed has previously been considered to be a consequence of physical decline but these results highlight the direct role of psychological state in predicting an objective aging outcome. Negative perceptions about aging are a potentially modifiable risk factor of some elements of physical decline in aging.
PUBLISHED
Keywords: aging; aging; Ageing